The Anglo-British imaginary and the rebuilding of the UK's territorial constitution after Brexit: unitary state or union state?. Issue 5 (3rd September 2022) - Wincott, Daniel; Murray, C. R. G.; Davies, Gregory
ABSTRACT: Brexit has foregrounded radical divergences between the accounts of the UK's constitutional order advanced by the UK Government and the devolved governments, with the distinctions coming into sharp relief in debates over legislation to sustain the UK's internal market. This article examines the limits to the roots of the UK Government's insistence that the UK is a unitary state, and not a union-state, in the textbook tradition of constitutional scholarship. Writers from A. V. Dicey to S. A. de Smith asserted that the UK was a unitary state largely as an adjunct to their accounts of parliamentary sovereignty. We also examine how the received orthodoxy of unitary accounts of the UK's constitution came under increasing pressure after the advent of devolution, but that the UK's membership of the European Union, and the operation of the principle of subsidiarity within European law, forestalled a considerable amount of constitutional contestation. The need to replace European law as a foundation of the UK internal market, and the UK Government's attempts to exert control over this transition, has produced a sustained debate about what the union means after Brexit.